Pulpectomy with rotary instrumentation in a pediatric patient: Case report - Pesantes Valarezo, María Isabela (2025)
Pulpectomy is the treatment of choice for primary teeth with severe pulp involvement, aiming to maintain the health of oral tissues and preserve the space for the permanent dentition. Rotary instrumentation is considered a technique currently used in primary dentition, as it allows for better adaptation to the shape of the canals, facilitates irrigation and subsequent obturation, reduces operative time, and improves pediatric patient cooperation during treatment.The objective of this study was to describe the clinical management of a pulpectomy in a primary tooth using rotary instrumentation in a pediatric patient. This case report presents the treatment of a primary first molar diagnosed with pulp necrosis, in which a pulpectomy with rotary instrumentation was performed. The Endo Kids system with Ni-Ti rotary files was used, irrigation was performed with sodium hypochlorite, and obturation was carried out using a calcium hydroxide and iodoform-based paste. A stainless-steel crown was placed as the final restoration, and three follow-up evaluations were conducted after the procedure.This case demonstrates the effectiveness of pulpectomy treatment using rotary instrumentation in primary teeth, showing both clinically and radiographically a good quality of obturation and canal sealing, and allowing for the preservation of the tooth in the oral cavity without infectious processes that could compromise the patient’s overall health.